2008
DOI: 10.1080/10641260802324685
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomics and Proteomic Approaches for the Study of Gamete Formation and Viability in Farmed Finfish

Abstract: The sustained mass production of alevins in finfish aquaculture requires a deep understanding of the biological processes controlling gametogenesis, which ultimately will determine the quality of eggs and sperm. Functional genomics and proteomics technologies have been recently developed, expanding the scope of biological investigation from studying single genes or proteins to studying potentially all genes and proteins at once in a systematic manner. The application of these methods in aquaculture is still in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 153 publications
0
25
0
Order By: Relevance
“…Consequently, a high percentage of buoyant eggs is often used as a marker of good quality, despite the fact that the physiological basis for poor or good egg quality in fish remains poorly understood. The investigation of the operant molecular mechanisms during oocyte hydration can contribute to fill this gap, as well as to identify valid markers for egg viability in marine fish (Cerdà et al , 2008). In addition, the definition of the role of Aqp1b and the intracellular regulatory pathways may contribute with the development of new cryopreservation methods for fish gametes and embryos based on aquaporin function (Chauvigné & Cerdà, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a high percentage of buoyant eggs is often used as a marker of good quality, despite the fact that the physiological basis for poor or good egg quality in fish remains poorly understood. The investigation of the operant molecular mechanisms during oocyte hydration can contribute to fill this gap, as well as to identify valid markers for egg viability in marine fish (Cerdà et al , 2008). In addition, the definition of the role of Aqp1b and the intracellular regulatory pathways may contribute with the development of new cryopreservation methods for fish gametes and embryos based on aquaporin function (Chauvigné & Cerdà, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, increasing knowledge about oogenesis is emerging in salmonids like rainbow trout (Oncorhynchus mykiss Walbaum) and coho salmon (Oncorhynchus kisutch Walbaum), as changes in the ovarian transcriptome during different stages of oogenesis have been studied with microarrays and suppression subtractive hybridization (SSH) (von Schalburg et al, 2005(von Schalburg et al, , 2008Bobe et al, 2006;MacKenzie et al, 2006;Luckenbach et al, 2008). Such studies have identified numerous participants that may be essential for oogenesis, greatly enhancing our knowledge of molecular mechanisms underlying this complex process in fish (Cerd a et al, 2008a). Nevertheless, large-scale studies on transcriptome dynamics during oogenesis are limited for marine species.…”
Section: Introductionmentioning
confidence: 99%
“…61 While most transcripts may be deposited in primary oocytes, the 62 oocyte transcriptome is dynamic, being influenced throughout 63 oogenesis by mRNA accumulation and degradation (reviews: 74 In humans and livestock, development up until MZT is fraught 75 with failure, making the transcriptomics of egg quality an active 76 area of biomedical and agricultural research (review: Ajduk and 77 Zernicka-Goetz, 2013). Because poor egg quality is a major limiting 78 factor in global aquaculture (see: Migaud et al, 2013), and with 79 zebrafish, Danio rerio, becoming a leading model for reproductive 80 transcriptomics (reviews: Mathavan et al, 2005;Aanes et al, 81 2011), research into fish ovary and embryo mRNA transcriptomes 82 has grown substantially in recent years (reviews: Lyman-83 Gingerich and Pelegri, 2007;Cerdà et al, 2008;Bobe and Labbe, 84 2010). Other types of RNA deposited in eggs, such as miRNA 85 (reviews: Mishima, 2012;Bizuayehu and Babiak, 2014) and long 86 noncoding RNA (lncRNA) (reviews: Pauli et al, 2012;Haque 87 et al, 2014), also play a role in regulating early development fishes has been rare.…”
mentioning
confidence: 98%